Role of the United Methodist Church towards environmental protection in Zimbabwe - Mburundu, Fortunate (Midlands State University, 2018)
The study explored the role of United Methodist Church towards environmental protection in Zimbabwe with particular reference to the activities done by most of the circuits in the church. Environmental protection has become a big issue in our day and age at local, national, regional and even at a global scale. The study was based on field study using observations, questionnaires with the United Methodist Church congregation encompassing the District Superintendents, circuits Pastors, circuits’ leaders including the evangelism committee and the general community members of Zimbabwe. Quantitative research methodology was used. The UMC plays a critical role in environmental protection through strategies such as clean up campaigns, environmental awareness, and tree planting and engaging with the environmental protection agencies such as EMA. This has greatly impacted the community through prevention of diseases such as cholera and malaria. The United Methodist Church has thus lived up to the church doctrine of keeping the Lord’s Earth’s habitable today and for future generations. There are thus advantages in undertaking environmental protection activities with a faith based commitment and hence feeling responsible to God in the efforts to achieve sustainable development